Exosomal microRNAs Targeting TP53 Gene as Promising Prognostic Markers for Head and Neck Squamous Cell Carcinoma - Jayaseelan, Vijayashree Priyadharsini; Arumugam, Paramasivam (Global Medical Genetics, 2022)
Statement of Problem MicroRNAs are small non-coding RNAs that regulate an array of functions by targeting crucial genes. A significant dysregulation in the TP53 profile has been observed in the head and neck squamous cell carcinoma (HNSCC) patients. Hence, the present in silico study was designed to identify those microRNAs which target TP53 gene and demonstrate their differential expression in HNSCC cases.Materials and Methods The study was extended further to explore their exosomal location using database such as EVmiRNA and ExoCarta. The study follows an observational in silico design. Computational tool miRDB was used identify the microRNA targets of TP53 gene. The UALCAN server was used to ascertain the expression of microRNA in HNSCC cases derived from the Cancer Gene Atlas dataset. The survival of HNSCC patients based on the differential expression microRNA markers were recorded. Further, each of the microRNA was queried for their exosomal presence using EVmiRNA.Results About 102 microRNA targets of TP53 gene with a target score in the range of 95–50 were identified. The differential expression data for 52 microRNAs was retrieved from the UALCAN database. The microRNAs hsa-miR-421, hsa-miR-548f-5p, and hsa-let-7c-5p were found to be differentially expressed with marked influence over the survival of HNSCC patients. Furthermore, hsa-miR-421 and hsa-let-7c-5p were found to have an exosomal origin especially in body fluids such as blood and saliva.Conclusion The results accumulated from the present study identified three microRNAs which can affect the functions of TP53 gene and bring about serious outcomes in HNSCC patients. The microRNAs of exosomal origin targeting TP53 gene in HNSCC patients can be a promising prognostic marker, which can be further used as a therapeutic lead by designing inhibitors.
Keywords: microRNAs; exosomes; TP53; HNSCC; theragnostic